1994
DOI: 10.3109/17453679408995442
|View full text |Cite
|
Sign up to set email alerts
|

The cement-canal prosthesis: A new cementation technique studied in cadaver femora

Abstract: To cite this article: Volkmar Jansson (1994) The cement-canal prosthesis: A new cementation technique studied in cadaver femora, Acta Orthopaedica Scandinavica, 65:2, 221-224,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…A number of investigations have focused on the importance of the quality of the bonecement interface created at the operation (Majkowski et al 1993, Jansson 1994, Juliusson et al 1994, Ritter et al 1994. Poor penetration of the cement into the trabecular bone caused by insufficient preparation and interposition of blood reduces the strength of the interface and may cause loosening.…”
mentioning
confidence: 99%
“…A number of investigations have focused on the importance of the quality of the bonecement interface created at the operation (Majkowski et al 1993, Jansson 1994, Juliusson et al 1994, Ritter et al 1994. Poor penetration of the cement into the trabecular bone caused by insufficient preparation and interposition of blood reduces the strength of the interface and may cause loosening.…”
mentioning
confidence: 99%
“…As the intramedullary pressure is likely to correlate positively with the number of embolic events [23], high peak pressures increase the risk of cardiopulmonary damage. However, to reach the recommended cement mantle of 2-5 mm in all areas [24], a pressure of approximately 2,000 mmHg is assumed to be sufficient [21,22]. Besides, Kapoor et al could show that a constant pressure, even though lower, is more important than a high peak pressure [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the conventional stem from which the cement injection stem is derived has shown good mid-term survival rates [33,34]. Furthermore, the cement mantle produced by the secondary cementing technique has been found to be effective [20,21], and an in-vivo long-term fatigue test has shown that the cement mantle was comparable or even significantly better than the conventional cemented stem [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations